46.1: Invited Paper: High Performance Micro LED Display Based on Complementary Metal‐Oxide‐Semiconductor Backplane by using Digital Driving Technology. (24th February 2021) - Shieh, Chen-Yu; Tsai, Chun-Wei; Lin, T. I.
Abstract : It is well known that the properties of micro LED display have the higher contrast ratio, higher brightness, high reliability, and much faster response time than conventional LCD and OLED displays. We demonstrate a prove of concept (POC) pico‐projector prototype with a F/0.9 camera lens, and green micro LED panel, and digital driving board. The lumen output from POC pico‐projector is only about 1 Lumen. We calculate that if the POC pico‐projector prototype is with much higher brightness, larger size micro LED panel, plus micro lens array, and three panels optical system, it should be able to achieve 500~600 Lumen pico‐projector.